(3GdTGajs - (3CMeO Hf eMeO Hf CMeO, CHh GdYHGS GdLQLGfj,J (B482 (3g` s ((3CMeO Ydi Hf CMeO Hf eMeO GdbQTi GdgcGQi s)
(3ChdgG (B:s
(3VQH HjfgeGZjQ eJaQbjf dCf Pdc djS HJaQb s
(3BNQgG (B:s
(3Je QHY GdeYGedGJ HMeO Gddg hefg hjJdhg ai GdQHY GdKGdK cJGH GdfcGM s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B214s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1023s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs